X-ray excited CsPb(Cl, Br)3 perovskite quantum dots-glass composite with long-lifetime. Issue 5 (May 2020) - Wang, Congyong; Lin, Hang; Zhang, Zhijun; Qiu, Zhihua; Yang, Hongyi; Cheng, Yao; Xu, Ju; Xiang, Xiaoqiang; Zhang, Liqiang; Wang, Yuansheng
Abstract: CsPbX3 (X = Cl, Br, I) perovskite quantum dots (QDs) have emerged as a kind of brand-new X-ray scintillator with high performance. Herein, following the phase transformation from amorphous to crystalline, CsPb(Cl, Br)3 QDs are in-situ precipitated from a borate glass matrix. It is demonstrated for the first time that the perovskite QDs-glass composite yields radioluminescence (RL), showing X-ray excited RL ∼1/18 to that of commercial Bi4 Ge3 O12 (BGO) single crystal. The color of RL is adjustable, dependent on the anionic species. Evidently, the high power X-ray induced damage in material is recoverable just by re-heating it at glass transition temperature. This work highlights the partial settlement of tough issues in perovskite QDs as scintillators, such as, physical stability, service lifetime, Pb-toxicity, and production scale.